Dileme duhovnikov v zgornjem posočju po drugi svetovni vojni skozi perspektivo tolminskega procesa - Klavora, Marko (Acta Histriae, 2009)
This contribution presents the "dilemmas" posed to priests from the upper Soča valley who remained in Yugoslavia after the end of WWII and the annexation of Primorska on September 15, 1947. The main part of the article discusses the main participants of the "Tolmin trial", which took place before the court in Tolmin between March 13 and 19, 1952. During the period after WWII, the authorities put overwhelming ideological and political pressure on the clergy - the "Tolmin trial" (and several other similar political trials after WWII) was an example of an uneven battle of organized authorities, as representatives of a certain ideology, against somewhat isolated individuals - priests - representing the Catholic Church which rejected the ideology in power. However, the aforementioned only describes a single level of occurrences. Another level, which certainly held some significance for individual priests in the upper Soča valley, was the shift in their social status, as they were assigned by the new authorities (or rather an attempt was made in this direction) a radically different role in relation to their environment from the one they used to play before WWII. However, this change proceeded neither as smooth nor as fast as was intended by the authorities. In the sense of the two levels indicated above, this article on priests who stayed in the upper Soča valley after the annexation in 1947 is largely an attempt to become aquainted with a certain (micro) experience, a perspective, and point of view. The article does not devote much attention to the establishment of the guilt or innocence of the priests convicted in the trials, but rather concentrates on the logic of the main source (trial material) as such: where was the focus of the authorities when investigating the potential guilt of imprisoned priests through the secret police (UDBA) activities? On the other hand, the author focuses primarily on the ways the priests tried to challenge the accusations on the part of UDBA about their activities during and after WWII while they were interrogated. The strategies of both sides are discussed.
Keywords: 1945-1953; Catholic Church; duhovniki; katoliška cerkev; politični procesi; tolminski proces; zgornje Posočje